Religious and Spiritual Coping and Post-traumatic Growth in Response to Youth’s Traumatic Grief and Loss - Hanna, Mariam (Université Saint-Paul / Saint Paul University, 2021)
Objective. For the past 20 years, spirituality has been gaining greater research attention. The literature has demonstrated that spirituality and religiosity have potential use as coping mechanisms in the face of stress and in fostering post-traumatic growth (PTG). The role of spirituality (defined as the connection to the transcendent, religiosity, and experiencing daily meaning) was examined in the face of traumatic grief and loss (TGL) in youth. It was hypothesized that spirituality would mediate the relation between TGL and PTG. Moreover, it was hypothesized that spirituality would mediate the relation between TGL and mental health. Methods. The data used for this study was derived from youth between the ages 17 and 24, from 47 participants. Participants were asked about their experience of spirituality as a connection to the transcendent and religiosity, spirituality in terms of daily meaning in life, TGL, PTG, and their mental health. Results. Spirituality predicted PTG. Moreover, it was shown that spirituality (specifically daily meaning) acted as a mediator between TGL and mental health. Conclusion. The findings support the relationships between spirituality, PTG, and mental health for youth.
Keywords: traumatic grief and loss (TGL); post-traumatic growth (PTG); spiritual and religious coping; youth; second wave positive psychology; mental health; daily meaning